The application in Spain of the opinionsof international committees: STS 1263/2018, an important turning point - Gutiérrez Espada, Cesáreo (CUADERNOS DE DERECHO TRANSNACIONAL, 2018)
The STS 1263/2018, of July 17, accepts the application in Spain of the opinion of an international committee created by a treaty of Spain is part, committee in respect of which our country expressly accepted its competence to resolve individual claims. And in accordance with its ruling, it condemns the State to pay compensation as reparation to the appellant for the moral damages suffered. With this sentence, our TS breaks with the previous situation and accepts the relevance in our national Law of the international commitments of Spain on rights and fundamental liberties of the person. Welcome, be it.
Keywords: effect in Spanish of the opinions of international committees; Angela Gonzalez Carreño; patrimonial responsability of the admmistration